Sociodemographic and academic profile of nursing students from four brazilian institutions - Susan Bublitz; Laura de Azevedo Guido; Raquel Soares Kirchhof; Eliane Tatsch Neves; Luis Felipe Dias Lopes
This study aimed to describe the sociodemographic and academic characteristics of nursing students from four Brazilian Educational Institutions. It is a prospective cross-sectional study. The data were collected between April 2011 and March 2012, through a survey form with questions about sociodemographic and academic characteristics of the students. The participants were graduate students enrolled in the nursing course, aged 18 years or older. 705 students participated, and these were mostly women, single, childless, who lived with their families, did not take part in sport activities and performed leisure activities. Also, most students do not participate in research groups, were not granted scholarships, are not employed, are satisfied with the course and do not intend to leave it. This study may become an important tool for the development of strategies that address the needs of students and also improve the quality of the teaching and learning process, reducing dropout rates.